2011
DOI: 10.1042/cs20100400
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 and atherothrombosis: relevance to pathophysiology and therapy

Abstract: IGF-1 (insulin-like growth factor-1) plays a unique role in the cell protection of multiple systems, where its fine-tuned signal transduction helps to preserve tissues from hypoxia, ischaemia and oxidative stress, thus mediating functional homoeostatic adjustments. In contrast, its deprivation results in apoptosis and dysfunction. Many prospective epidemiological surveys have associated low IGF-1 levels with late mortality, MI (myocardial infarction), HF (heart failure) and diabetes. Interventional studies sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 321 publications
(370 reference statements)
1
52
1
Order By: Relevance
“…A number of epidemiological studies have suggested that IGF-I levels in the lower normal range are associated with an increased risk of ischemic heart disease, stroke, hypertension, reduced glucose tolerance, and diabetes (II, [21][22][23][24]. Although the relationship between IGF-I and cardiovascular disease is still unknown, a protective role in the development of atherosclerosis was suggested for free IGFI levels (24).…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological studies have suggested that IGF-I levels in the lower normal range are associated with an increased risk of ischemic heart disease, stroke, hypertension, reduced glucose tolerance, and diabetes (II, [21][22][23][24]. Although the relationship between IGF-I and cardiovascular disease is still unknown, a protective role in the development of atherosclerosis was suggested for free IGFI levels (24).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial progenitor cells (EPCs), which are derived from bone marrow or vessel walls, promote vessel repair and prevent endothelial dysfunction (Conti et al 2011, Higashi et al 2012. They may differentiate to form a new endothelium or act as paracrine sources of cytokines and growth factors to enhance endothelial repair.…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Although IGF-I activity appears to play a pacesetter role in the aging process, and is sometimes referred to as a universal cancer promoter, it does however have a direct favorable impact on vascular endothelial function and endothelial precursor cells, and its dietary downregulation might therefore have a countervailing negative impact on vascular health (Perticone et al 2008;Csiszar et al 2008;Conti et al 2011;Devin and Young 2008)-an effect which might have a greater impact on health in aging humans than in rodents. It seems unlikely, however, that IGF-I's impact on the vasculature played an important role in the lower mortality associated with higher protein intakes among the elderly in the NHANES III analysis, as, among those over 65, plasma IGF-I levels did not differ significantly as a function of protein intake (Levine et al 2014).…”
mentioning
confidence: 99%